Availability modeling of terrestrial hybrid FSO/RF based on weather statistics from tropical region - Basahel, Ahmed A; Islam, Md Rafiqul; Habaebi, Mohamed Hadi; Zabidi, Suriza Ahmad (Institution of Engineering and Technology (IET), 2020)
Free-space optical (FSO) communication links are point-to-point wireless technologies. It provides high data rates up to gigabit per second. FSO link availability is easily affected by different weather conditions. Radio-frequency (RF) can be a complimentary link to the FSO link to increase the availability. Hybrid FSO/RF is a feasible technology for providing high availability of point-to-point wireless links. In tropical regions, normally RF link is relatively sensitive to rain. Availability prediction of hybrid FSO/RF with the selection of suitable RF is indispensable, especially in tropical regions. In this paper, empirical models are proposed to predict the link availability of RF, and hybrid FSO/RF over link ranges up to 5 km. The availability prediction models are based on long-term statistics of atmospheric attenuations from the tropical climate zone. The RF link availability prediction model is developed for frequency ranges from 10 GHz to 100 GHz using the ITU-R rain attenuation model. It is link distance, fade margin, and radio frequency dependent. The proposed availability models can predict carrier as well as enterprise class availability. The availabilities predicted by proposed models are found in good agreement with those estimated by ITU-R.